P374 Front loading infliximab dosing regimen improves outcomes in Crohn's Disease perianal fistulas. (21st January 2022) - Lloyd, A; Wilkinson, A; Aleman Gonzalez, H; Ramachandran, S; Whitehead, E; Pattinson, A; Stamp, K; Turnbull, J; Talbot, A; Sebastian, S
Abstract: Background: Higher infliximab maintenance trough levels are found to be associated with higher perianal fistula healing rates in Crohn's Disease. The relevance of accelerated front loading dosing in perianal fistula has not been determined. This study aimed to establish whether front loading with a higher dose infliximab regime at induction is associated with better fistula outcomes. Methods: Crohn's Disease patients with perianal fistulas treated with infliximab in a tertiary referral centre IBD unit were included. Patients were categorised as standard or front loading based on induction dose infliximab of, 5mg/kg or, 10mg/kg. The target for infliximab maintenance trough levels was >10mcg/mL. The primary outcome was the need for reintervention (defined as repeat abscess drainage, seton re-insertion, diverting stoma or proctectomy) at, 12 months post initiation of treatment. Secondary outcomes were the proportion of patients having clinical healing, radiologic healing and combined clinical and radiologic healing. Drug levels post induction and post first maintenance were evaluated. The proportion of patients needing dose escalation or de-escalation were also assessed. Chi-squared or Fisher exact tests were used to compare categorical variables and Kaplan-Meier survival curves were plotted for re-intervention free survival. Results: Seventy-nine patients were included in analysis (Males: Females, 36:43, median age with fistula = 31). Seventeen (22%) of patients received a front loading dose of, 10mg/kg while sixty-two (79%) patients received the standard dose of, 5mg/kg among whom, 70% had dose escalation. Need for reintervention was significantly lower in patients who received a front loading dosing schedule compared to the standard dose (2/17 (12%) vs, 26/62 (42%), p=0.02) (Figure, 1). Higher clinical fistula healing rates were observed with front-loading dosing (82% vs, 45%, p=0.008). Radiologic healing in those who had follow up Magnetic Resonance Imaging (MRI) was not significant between both groups (8/17 (47%) vs, 20/62 (32%), p=0.133). Target therapeutic infliximab levels at maintenance was achieved in, 14/17 (82% of the patients receiving front loading dosing, while this was achieved in only, 2 of the, 43 (5%) tested patients with standard dosing. Reintervention requirement rates were higher in those patients with suboptimal maintenance levels (17/44 (39%) vs, 2/16 (12.5%), p=0.01). The Kaplan-Meier curves confirm that the front loading dosing regimen does prevent the need for reintervention (p=0.03) (Figure 2). Figure1: Figure 2: Conclusion: Front loading with higher infliximab dose achieves better fistula healing and reduce the need for reinterventions in Crohn`s disease with perianal fistula.